STRATEGI PEMBENTUKAN KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR TAHUN 2002-2011 - Muhammad Bakri; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The title of this research is Kubu Sub Formation Strategy BabussalamRokan Hilir Year 2002-2011 Based on the discovery of the phenomenon thatoccurred in the field, namely lack of response from the Regent of Rokan Hilir indoing or making division in the district of Kubu Kubu district is divided intoBabussalam In 2002, after the Kubu district communities bargaining andconsultation with district head, headman, and community leaders to discuss themulti-purpose halls on the division of Kubu district into Babussalam Kubudistrict. Where the results of its deliberations were submitted to the Regent ofRokan Hilir Kaputen in 2002. This is because the village in the district of KubuBabussalam not enough to qualify bloomed. The type used in this research isdescriptive qualitative survey techniques. Data collection techniques used in thisstudy was the observation, field notes, documentation and interviews withinformants research. The research location is in the district of Kubu BabussalamRokan Hilir.Based on results of the analysis of the data of research to uncover andanswer research questions can be concluded that the action strategies undertakenin the District Formation Babussalam Kubu Rokan Hilir Year 2002-2011 is an actof deliberation which in the deliberations dilibat parties instrumental in theexpansion Kubu Sub Babussalam Rokan Hilir as Member of parliament RokanHilir in 2002 and 2011 Mr Amansyah Mr Bukhoiri, Chairman of the SpecialCommittee V, Head Kubu, Community Leaders and Community Kubu KubuBabussalam from 2002 to 2011. in the meeting it was concluded that Kubu districtBabussalam bloomed. Redistricting Babussalam Kubu district governmentproposed to Parliament Rokan Hilir discussion has been done three times. Andmembers of the special committee has been reviewing five straight up untilkepenghuluan.Keywords: Strategy, Formation, District.